Right to Inclusive Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Increasing the availability of human rights and freedoms has recently received significant attention in the Republic of Uzbekistan, as it does in all democratic nations. The state has a responsibility to properly uphold the rights of people with disabilities. In order to guarantee the right of individuals with exceptional educational needs to access education, particularly higher education, this article explores several organizational and legal issues and makes solutions for them.